1990
DOI: 10.1182/blood.v76.12.2594.2594
|View full text |Cite
|
Sign up to set email alerts
|

t(3;21)(q26;q22): a recurring chromosomal abnormality in therapy- related myelodysplastic syndrome and acute myeloid leukemia

Abstract: We have identified an identical reciprocal translocation between the long arms of chromosomes 3 and 21 with breakpoints at bands 3q26 and 21q22, [t(3;21)(q26;q22)], in the malignant cells from five adult patients with therapy-related myelodysplastic syndrome (t-MDS) or acute myeloid leukemia (t-AML). Primary diagnoses were Hodgkin's disease in two patients and ovarian carcinoma, breast cancer, and polycythemia vera in one patient each. Patients had been treated with chemotherapy including an alkylating agent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 0 publications
1
42
0
2
Order By: Relevance
“…Our study and the recent work of others (Nucifora et al, 1993c;Mitani et al, 1994) provide evidence of molecular heterogeneity in the (3;21) (q26;qZZ) associated with various leukemia subtypes (Schneider et al, 1991). T h e t(3;21) is found in the blastic crisis of CML (Rubin et al, 1987;Coyle and Nayfeld, 1988), in leukemia evolving from (therapy-related) myelodysplasia (Rubin et al, 1990), and in leukemia following other hematopoietic proliferative diseases (Dastugue et al, 1990). It has been suggested that the t(3;21) has a b 0 -C TTG GGG CIG GTA CAC CCl' CC4 Gcx: TGG TAC ACC CTC CAG G C T GGT AT.4 Crc AGG GAC CAT GTC TCA )His Leu G l y Leu V a l His Pro Pro G l y T r p '&r Thr Leu G l n A l a G l y Ile Leu Arg Asp His V a l Ser GAT 'TCC TE GGT TCA ACC T I T CCC CCA GGG GGA 'IW: C>G GCC CCC GTA h4G CCA 9.AA AGT )Asp Ser Leu G l y Ser Thr Phe Pro Pro G l y G l y T r p G l n A l a Pro V a l L y s Pro L y s Ser critical role in the progression from a preleukemic to a leukemic state since it has rarely been observed in de novo acute myelocytic leukemia (Rubin et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Our study and the recent work of others (Nucifora et al, 1993c;Mitani et al, 1994) provide evidence of molecular heterogeneity in the (3;21) (q26;qZZ) associated with various leukemia subtypes (Schneider et al, 1991). T h e t(3;21) is found in the blastic crisis of CML (Rubin et al, 1987;Coyle and Nayfeld, 1988), in leukemia evolving from (therapy-related) myelodysplasia (Rubin et al, 1990), and in leukemia following other hematopoietic proliferative diseases (Dastugue et al, 1990). It has been suggested that the t(3;21) has a b 0 -C TTG GGG CIG GTA CAC CCl' CC4 Gcx: TGG TAC ACC CTC CAG G C T GGT AT.4 Crc AGG GAC CAT GTC TCA )His Leu G l y Leu V a l His Pro Pro G l y T r p '&r Thr Leu G l n A l a G l y Ile Leu Arg Asp His V a l Ser GAT 'TCC TE GGT TCA ACC T I T CCC CCA GGG GGA 'IW: C>G GCC CCC GTA h4G CCA 9.AA AGT )Asp Ser Leu G l y Ser Thr Phe Pro Pro G l y G l y T r p G l n A l a Pro V a l L y s Pro L y s Ser critical role in the progression from a preleukemic to a leukemic state since it has rarely been observed in de novo acute myelocytic leukemia (Rubin et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Rearrangements of the long arm of chromosome 3, involving the 3q21 and 3q26.2 regions, have been observed in de novo acute myeloid leukemia (AML), AML with antecedent myelodysplastic syndrome and aggressive subtypes of myelodysplasia (MDS) [1–4]. Although several nonrandom, recurrent translocations involving 3q21 and 3q26.2 have been described, the most common rearrangements involve simultaneous disruption of 3q21 and 3q26.2 as the result of inv(3)(q21q26.2) [inv(3)], t(3;3)(q21;q26.2) [t(3;3)], and less commonly ins(3;3)(q26.2;q21q26.2) [ins(3;3)] [5–9]. The end result of each of these rearrangements is the juxtaposition of the RPN1 gene at 3q21 with the EVI1 ( MECOM ) gene at 3q26.2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although several genes structurally or transcriptionally altered by translocations have been identified, the molecular mechanisms underlying such translocations are poorly understood. The t(3;21)(q26;q22) is a recurring abnormality in blastic crisis of chronic myelogenous leukemia (CML) (Rubin et al, 1987;Coyle and Najfeld, 1988), leukemia developed from myelodysplastic syndrome (MDS; Rubin et al, 1990), and therapy-related leukemia (Dastugue et al, 1990), but rarely occur in de novo acute myelogenous leukemia (AML; Rubin et al, 1990), suggesting that the appearance of this chromosomal abnormality may be a key event when hematological disorders transform to acute leukemia (Chen et al, 1991). Molecular cloning and cytogenetic analysis indicate that the breakpoints are heterogeneous even within a specific clinical phenotype (Nucifora et al, 1993(Nucifora et al, , 1994Mitani et al, 1994;Sacchi et al, 1994).…”
mentioning
confidence: 99%
“…Notably, the t(3;21) breakpoints involve the AML1 gene known to be rearranged in t(8;21) associated with AML (Miyoshi et al, 1991;Mitani et al, 1994) and in t(12;21) associated with acute lymphoblastic leukemia (ALL) (Golub et al, 1995;Romana et al, 1995). Although t(8;21) and t(12;21) are frequently detected in de novo AML and ALL, respectively, t(3;21) is frequently associated with therapy-related AML (Keldsen et al, 1987;Rubin et al, 1990;Quesnel et al, 1993). These findings suggest that the genetic recombination mechanisms causing the 21q22 translocation may be different among the translocations of de novo AML, blastic crisis of CML, and therapyrelated leukemias.…”
mentioning
confidence: 99%